Pentingnya Bahasa Arab Dalam Mengembangkan Pemahaman Islam yang Mendalam: Analisis Tentang Metode Pembelajaran dan Penerapannya - Mufadhol, Allam Tri; Nuraeni, Neni (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Arabic plays a crucial role in developing a deep understanding of Islam, owing to its status as both the language of revelation and knowledge in Islamic scholarship. Mastery of Arabic is fundamental for accurately accessing and interpreting Islamic texts such as the Qur’an, Hadith, jurisprudence, and exegesis. Various applied teaching methods—from Grammar-Translation and Communicative Language Teaching to Content-Based Instruction—demonstrate that combining traditional and modern approaches yields optimal learning outcomes. The integration of technology, including digital applications and e-learning, further enhances the effectiveness of Arabic language learning, especially in supporting contemporary Islamic studies. Competency evaluation in Arabic requires a comprehensive and adaptive approach that responds to the demands of modern times and students’ multiple intelligences. Contextual, interactive, and motivation-based Arabic learning has been proven to improve understanding and internalization of Islamic values, both practically and academically.